Reestablishment of Active Immunity against HBV Graft Reinfection after Liver Transplantation for HBV-Related End Stage Liver Disease. (17th December 2014) - Lu, Shi-Chun; Jiang, Tao; Lai, Wei; Liu, Yuan; Zhang, Jing; Zeng, Dao-Bing; Li, Chuan-Yun; Wang, Meng-Long; Lin, Dong-Dong; Zhu, Yue; Li, You-Ping; Li, Ning
Abstract : Background . The aim of this study was to establish a hepatitis B virus (HBV) vaccination protocol among orthotopic liver transplantation (OLT) recipients under the coverage of a low-dose hepatitis B immunoglobulin (HBIG) combined with an antiviral agent prophylaxis protocol. Method . Two hundred OLT recipients were included in this study. The vaccine was injected at months 0, 1, 2, and 6. Low-dose HBIG combined with antiviral agent prophylaxis protocol was continued before reestablishment of active immunity against HBV in order to maintain a steady anti-HBs titer. Results . Active immunity against HBV was reestablished in 50 patients, for an overall response rate of 25%. Of the 50 patients, 24 discontinued HBIG without any HBV graft reinfection during a follow-up period of 26.13 ± 7.05 months. 21 patients discontinued both HBIG and antiviral agents during a follow-up period of 39.86 ± 15.47 months, and 4 patients among them appeared to be HBsAg positive. There was no recipient death or graft loss because of HBV reinfection. Conclusions . Vaccination preventing HBV reinfection for OLT recipients is feasible. The strategy withdrawal of HBIG with induction of active immunity against hepatitis B is reasonable for long-term survivors of OLT; however, discontinuation nucleoside analogues should be cautious.